2003
DOI: 10.1182/blood-2003-05-1522
|View full text |Cite
|
Sign up to set email alerts
|

α5β1 integrin as a cellular coreceptor for human parvovirus B19: requirement of functional activation of β1 integrin for viral entry

Abstract: Replication of the pathogenic human parvovirus B19 is restricted to erythroid progenitor cells. Although blood group P antigen has been reported to be the cell surface receptor for parvovirus B19, a number of nonerythroid cells, which express P antigen, are not permissive for parvovirus B19 infection. We have documented that P antigen is necessary for parvovirus B19 binding but not sufficient for virus entry into cells. To test whether parvovirus B19 utilizes a cell surface coreceptor for entry, we used human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
157
1
7

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(167 citation statements)
references
References 39 publications
2
157
1
7
Order By: Relevance
“…We have previously reported that the necessary cellular receptor for B19V infection is globoside (P antigen) (2), and others have reported coreceptors to be ␣5␤1 integrin (37) and/or autoantigen Ku80 (17). The permissiveness to B19V infection of the cells relies primarily on viral entry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that the necessary cellular receptor for B19V infection is globoside (P antigen) (2), and others have reported coreceptors to be ␣5␤1 integrin (37) and/or autoantigen Ku80 (17). The permissiveness to B19V infection of the cells relies primarily on viral entry.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies to CD34 (BD Biosciences, Franklin Lakes, NJ), CD36 (BD Biosciences), GPA (BD Biosciences), and CD71 (BD Biosciences) were used for phenotyping. Antibodies against globoside (Matreya, Pleasant Gap, PA), CD49e (BD Biosciences), and KU80 (Calbiochem, San Diego, CA) were used for the detection of B19V cellular receptors (17,37). Flow cytometry was performed using the Beckman Coulter Cytomics FC 500 flow cytometry system (Beckman Coulter, Fullerton, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Although the P antigen is necessary for binding of the virus to the cell surface, it is not sufficient for entry and replicative infection in human cells (22,23). Recent studies support the existence of a cellular co-receptor, ␣5␤1 integrin, for successful infection (24), although this remains controversial. This integrin is expressed at high levels on erythroid progenitors, whereas P antigen-positive nonerythroid cells that do not express this co-receptor are considered non-permissive for efficient infection.…”
Section: Pathogenesis and Immune Responsementioning
confidence: 99%
“…The viral genome encodes five known, and a possible sixth, protein products: VP1 and VP2 that compose the viral capsid, NS1, the main replicative protein, and two or three smaller proteins of unclear function (7.5 kDa, 11 kDa, and an open reading frame for the putative X protein) [10][11][12]. In addition to erythroid precursor cells, which are permissive for viral replication, B19V can infect a number of different cell types, utilizing the globoside or blood group P-antigen as a receptor13 along with α5β1 integrin [14]. After entry, the viral DNA is shuttled to the nucleus with the host-encoded DNA repair protein Ku80 [15] where replication and transcription occur concurrently following initial conversion of the viral DNA to double-stranded DNA [16,17].…”
Section: B19 Genome Structurementioning
confidence: 99%
“…The single-stranded DNA genome of B19 is packaged into a nonenveloped, icosahedral protein shell of 280 Å in diameter [14]. The capsid consists of 60 structural subunits, 95% of which is the major viral protein VP2 (58 kDa) [15].…”
Section: B19 Genome Structurementioning
confidence: 99%